A q-Analog of the Hua Equations - Bershtein, O.; Sinel’shchikov, S. (Журнал математической физики, анализа, геометрии, 2009)
A necessary condition is established for a function to be in the image of a quantum Poisson integral operator associated to the Shilov boundary of the quantum matrix ball. A quantum analogue of the Hua equations is introduced.